2017
DOI: 10.1002/elan.201600755
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Poly (N‐isopropylacrylamide) Coated SiO2 Core‐shell Microspheres via Surface‐initiated Atom Transfer Radical Polymerization for H2O2 Biosensor Applications

Abstract: In this study, inorganic/organic composites containing poly (N‐isopropylacrylamide) coated core‐shell SiO2 microspheres were prepared via surface‐initiated atom transfer radical polymerization (ATRP). The thermal responsive polymer, N‐isopropylacrylamide was treated with methanol, water and CuBr/CuBr2/1,1,4,7,7‐pentamethyldiethylenetriamine (PMDETA) at room temperature to form PNIPAM@SiO2 microspheres. The as‐prepared PNIPAM@SiO2 microspheres were characterized by FT‐IR, TGA, XPS, SEM, TEM analyses. Hemoglobin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…The performance of the present GC/GNNS-S electrode towards the sensing of Nb was compared with the recently reported papers (Table S3, ESI†). 19,25–37 The inspection of Table S3 (ESI†) indicates that most of the reported sensors for Nb were based on nanocomposites. The preparation of these nanocomposites not only involves several steps but also adopts tedious procedures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of the present GC/GNNS-S electrode towards the sensing of Nb was compared with the recently reported papers (Table S3, ESI†). 19,25–37 The inspection of Table S3 (ESI†) indicates that most of the reported sensors for Nb were based on nanocomposites. The preparation of these nanocomposites not only involves several steps but also adopts tedious procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the sensors fabricated from SSG-AuAg and EDAS/g-C 3 N 4 -Ag are expensive. 25,34 However, the fabrication of the present sensor based on GNNS-S is very easy involving simple procedures and very importantly it is less expensive. Besides, it showed the highest LOD in contrast to the papers listed in Table S3 (ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…These applications include the immobilization of different adsorbents for separations and/or removal of different compounds, such as dyes, heavy metals, and bovine serum albumin, the immobilization of catalysts and enzymes for increasing thermal stability, enhanced activity and ease of recovery, the modification of membranes for control of selectivity and biofouling, and the fabrication of superhydrophilic and superhydrophobic surfaces (including sprayable superhydrophobic coatings) . Nanoparticles modified with polymers also have been used as sensors (e.g., to detect H 2 O 2 ), fabricating anti‐biofouling surfaces, and for the preparation of hemocompatible surfaces in order to prevent blood coagulation …”
Section: Introductionmentioning
confidence: 99%
“…The obtained materials were core shell-like structure and showed the good thermoresponsive property. It was suggested that they were applicable to the fields of biological and biomedical fields [19,20]. In another strategy, using sol-gel process was a sequence of numerous SiO2 particles embedded with PNIPAM particles at room temperature [20].…”
mentioning
confidence: 99%